Acting natural: television and David Foster Wallace's metaffective fiction. Issue 11 (2nd November 2022) - Judy, Ron S.
ABSTRACT: This article looks at three important early works about television by David Foster Wallace that are not often studied in tandem: the stories 'Little Expressionless Animals' (1988) and 'My Appearance' (1988), and the long essay on television and American fiction, 'E Unibus Pluram: Television and Contemporary U.S. Fiction' (1993). The analysis attempts to show how Wallace's 'metaffective fiction' (Clare 2018) explores important assumptions about the role of emotions and affect in the production of literary works. Relying chiefly on affect theory, I study these early works' depiction of television (i.e. the shows 'Jeopardy' and 'Late Night with David Letterman' respectively) as a world of hyper-self-consciousness that nevertheless possess the potential for authentic emotional response and adjustment. The article also tries to assess how Wallace's writing emphasises the relationship between affective writing's potential and the ways in which popular culture enables or disables our capacity for emotional responsiveness. Moreover, it also claims that in these works Wallace goes beyond the postmodern notion of a 'waning of affect' (Jameson 1990) under late capitalism to imagine a post-postmodernist fiction driven instead by an 'intensification of affect'; that is, in the distorting imaginative space of television Wallace discovers how metaffective fiction (Clare 2019) can enable a suspension of disbelief that disrupts hyper-ironic postmodern self-consciousness and enables more authentic modes of expression and acting to emerge.